Interleukin-6 Enhances Production of Anti-OspC Immunoglobulin G2b Borreliacidal Antibody - Remington, Monica C. (American Society for Microbiology, 2001)
Protection against infection with Borrelia burgdorferi is dependent primarily on induction of complement-dependent antibody that can kill the spirochete. Measuring the production of sustained high levels of borreliacidal antibody is thus paramount for determining potential vaccine efficacy. We investigated the borreliacidal antibody response in sera and the amount of antibody produced by cultured lymph node cells of C3H/HeJ mice vaccinated with outer surface protein C (OspC). We showed that recombinant OspC was a weak stimulant of borreliacidal antibody production compared to whole cells of OspC-expressing B. burgdorferi. Mice vaccinated with B. burgdorferi in adjuvant produced a high level (titer, 5,120) of anti-OspC borreliacidal antibody, which waned rapidly. Similarly, borreliacidal antibody production by cultured lymph node cells from vaccinated mice peaked soon after vaccination and then decreased. Treatment of lymph node cells with interleukin-6 (IL-6) augmented borreliacidal antibody production, particularly immunoglobulin G2b, whereas treatment with anti-IL-6 inhibited the borreliacidal response. These findings demonstrate a previously unrecognized role for IL-6 in borreliacidal antibody production that may have important implications for vaccine development.